Characterisation of an inverted X chromosome (p11.2q21.3) associated with mental retardation using FISH. Issue 2 (February 1998) - Sloan-Béna, F; Philippe, C; LeHeup, B; Wuilque, F; Levy, E R; Chéry, M; Jonveaux, P; Monaco, A P
Abstract : We report on a patient with a pericentric inversion of the X chromosome, 46, Y, inv(X) (p11.2q21.3), who was referred for cytogenetic analysis because of mild mental retardation, short stature, prepubescent macro-orchidism, and submucous cleft palate. The same chromosomal abnormality was found in the proband's mother. The inverted X chromosome was late replicating in all the mother's lymphocytes studied, indicative of a likely unbalanced inversion. We show, by fluorescence in situ hybridisation (FISH) using a panel of ordered yeast artificial chromosome (YAC) clones, that the Xp breakpoint is localised in Xp11.23 between DXS146 and DXS255 and that the Xq breakpoint is assigned to the X-Y homologous region in Xq21.3. YACs crossing the Xp and Xq breakpoints have been identified. One of these two breakpoints could be linked to the mental retardation in this patient as many non-specific mental retardation (MRX) loci have previously been located in the pericentromeric region of the X chromosome. Morever, the elucidation at the molecular level of this rearrangement will also indicate if cleft palate or prepubescent macro-orchidism, or both, in this boy are related to one of the two X breakpoints.